Dynamic strain determination using fibre-optic cables allows imaging of seismological and structural features - Philippe Jousset (Nature Portfolio, 2018)
Imaging the internal structure of faults remains challenging using conventional seismometers. Here, the authors use fibre-optic cables used for telecommunications to obtain strain data and identify faults and volcanic dykes in Iceland and suggest that fibre-optic cables could be used for hazard assessment.